(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Obesity and vitamin D deficiency are linked in a substantial way. More research into the mechanism of vitamin D insufficiency is required to analyze this link. The purpose of this review was to examine the published literature on the relationship between obesity and vitamin D deficiency. Obese people are frequently less exposed to sunlight due to their lack of exercise, and the huge size of the fat mass may limit vitamin D production under the skin, where vitamin D is processed in the adipocytes. Vitamin D insufficiency affects adipocyte growth and differentiation consequently weight gain. Several researches have been conducted to investigate the impact of obesity on developing vitamin D insufficiency. Because research on the effect of vitamin D and obesity is still scarce, this study intended to compile studies that explain this effect and brings as many points of view as possible together.